MANAJEMEN PEMASARAN JAMUR TIRAM KELOMPOK WANITA TANI SRIKANDI PANGAN ADILUWIH BERBASIS MEDIA SOSIAL FACEBOOK - Fauzi (Jurnal PkM Pemberdayaan Masyarakat, 2020)
KWT Srikandi Pangan including those engaged in oyster mushroom entrepreneurship in developing oyster mushroom marketing by following current technological developments, it is necessary to have an online sales system through social media. Information about the oyster mushrooms, benefits, processed oyster mushrooms, and purchase registration is available in this online sales system. The development of this system has resulted in a Facebook-based online sales system that serves purchases at retail prices and also baskets prices according to message needs. It is hoped that orders can increase rapidly with the online sales system that has been built. The steps that will be taken are 1) Creating an account, 2) Socializing the use of accounts and promotional methods through social media, 3) Assistance during activities.